ACTIVITIES OF TRADE UNIONS IN KARAKALPAKSTAN IN THE 70S OF THE 20TH CENTURY AND TRAIR ROLE IN SOCIETY - Erniyazova, Dilorom Bekniyazovna (SCIENCE and SOCIETY, 2026)
This article analyses the socio-political activities of trade unions in the Karakalpak Autonomous Soviet Socialist Republic during the 1970s, their role in labour relations, and their influence on public life. The study is based on existing literature on Soviet-era trade unionism, secondary sources drawing on archival materials, and scholarly theoretical approaches. The article examines the main areas of trade union activity, their organisational structure and relations with the working class, and assesses the regional distinctiveness of these organisations within the broader Soviet context.
Keywords: trade unions; Karakalpakstan; Soviet period; labour relations; social policy; ASSR; 1970s; industry; working class